2019
DOI: 10.1021/acscatal.8b04846
|View full text |Cite
|
Sign up to set email alerts
|

Unpicking the Cause of Stereoselectivity in Actinorhodin Ketoreductase Variants with Atomistic Simulations

Abstract: Ketoreductase enzymes (KRs) with a high degree of regio-and stereoselectivity are useful biocatalysts for the production of small, specific chiral alcohols from achiral ketones. Actinorhodin KR (actKR), part of a type II polyketide synthase involved in the biosynthesis of the antibiotic actinorhodin, can also turn over small ketones. In vitro studies assessing stereocontrol in actKR have found that, in the "reverse" direction, the wild-type (WT) enzyme's mild preference for S-α-tetralol is enhanced by certain … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 87 publications
4
22
0
Order By: Relevance
“…Coming to the study of the activity of HSDHs toward non-steroidal substrates, we have confirmed that enzymes evolved to accommodate structurally complex and bulky substrates in their active sites, maintain their selectivity towards much simpler molecules, as observed with compounds 1, 2 and 5. These results corroborate the few scant previous literature reports, point out the importance of having in hands libraries of enzymes and encourage us to continue these studies in order both to acquire more information on the general substrate scope of HSDHs and to exploit molecular modeling approaches [53] to find suitable rationales for the observed selectivity.…”
Section: Discussionsupporting
confidence: 88%
“…Coming to the study of the activity of HSDHs toward non-steroidal substrates, we have confirmed that enzymes evolved to accommodate structurally complex and bulky substrates in their active sites, maintain their selectivity towards much simpler molecules, as observed with compounds 1, 2 and 5. These results corroborate the few scant previous literature reports, point out the importance of having in hands libraries of enzymes and encourage us to continue these studies in order both to acquire more information on the general substrate scope of HSDHs and to exploit molecular modeling approaches [53] to find suitable rationales for the observed selectivity.…”
Section: Discussionsupporting
confidence: 88%
“…Rigid docking calculations of act KR–NADPH and apo act ACP were performed using the Bristol University Docking Engine (BUDE), 42 with GPU acceleration. The structure for act KR–NADPH was obtained from previous simulations 27 starting from PDB ID 2RH4, 8 and the structure of act ACP was taken from model 13 of the NMR ensemble PDB ID 2MVU, 25 wherein the octaketide mimic is most unsheathed into the solvent (further details in Supporting Information ). To maximize docking efficiency, the search space was restricted to areas of each protein’s accessible surface interfaces and excluded areas too far away from the arginine patch.…”
Section: Methodsmentioning
confidence: 99%
“…The QM region was treated with the semiempirical method PM6 60 as used and benchmarked in our previous study on act KR (PM6 overestimates the barrier, but the mechanism is correct). 27 QM/MM MD US simulations of reductive hydride transfer from NADPH to 2 ’s C9 were run as previously reported, 27 using the difference ( x – y ) as the reaction coordinate, where y is the distance NADPH: H – – 2 /C9 and x is the distance NADPH: H – –NADPH/C H– ( Figure S2 ). Simulations were started from 11 or 12 different “reactive” or “reaction competent” conformations selected from stage II MD runs for each of the three isomers of 2 for which reaction competent conformations were regularly sampled (vide infra).…”
Section: Methodsmentioning
confidence: 99%
“…Manufacture of commercially valuable polyketides, secondary metabolites synthesized by multi-domain polyketide synthase complexes, has been investigated via comparison of thioesterase binding affinity to cyclized products to understand product release mechanisms of the antifungals amphotericin and nystatin (Wang et al, 2021). Binding free energy analysis is also used to elucidate the molecular basis of ketoreductase chain length and regiospecificity (Serapian and van der Kamp, 2019;Zhao et al, 2020). Potential insecticides targeting the ecdysone receptor to disrupt growth are identified (Horoiwa et al, 2019).…”
Section: Non-pharmaceutical Applicationsmentioning
confidence: 99%